Feminism counseling in handling catcalling victims - Maulidya, Intan Nurfika; Qomar, Subaidi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
Catcalling is a form of sexual harassment occurs in public spaces, so it has an impact on victims, who are primarily women. The impact felt by the victim is not visible physically but psychologically, such as the emergence of feelings of fear, anxiety, discomfort, disgust, and even a deep sense of trauma. The research was conducted using a descriptive qualitative method with a microscopic approach and using the theory of Feminism, which is centred on women. The purpose of writing this article is to describe verbal sexual violence and provide knowledge about the prevalence of catcalling and the impact of it in society. The catcalling phenomenon seems ordinary and commonplace in society, so it is very meaningful to discuss; the more often the phenomenon occurs, the more victims there will be. The study results show that society still tolerates catcalling; it is considered even a compliment or a joke.